Transvaginal sonographic evaluation at different menstrual cycle phases in diagnosis of uterine lesions - Hajishaiha M; Ghasemi-rad M; Karimpour N; Mladkova N; Borom; F (Dove Medical Press, 2011)
Masomeh Hajishaiha1, Mohammad Ghasemi-rad2, Nazila Karimpour1, Nikol Mladkova3, Farzaneh Boromand11Department of Gynecology, 2Student Research Committee (SRC), Urmia University of Medical Sciences, Urmia, Islamic Republic of Iran; 3Institute of Cell and Molecular Science, London, UKPurpose: Intrauterine lesions (IULs) are a common finding in women of reproductive age, particularly infertile women. Transvaginal sonography (TVS) is a popular tool for IUL detection, but there are conflicting data with respect to its accuracy.Methods: Five hundred and six women were enrolled into the study. Of these, 496 underwent hysterosalpingography and subsequent TVS six different times during the course of their menstrual cycle. If a lesion was detected, it was further evaluated by sonohysterography (SHG) and hysteroscopy.Results: Of 496 women, 41 were shown to have IULs by TVS and those lesions were confirmed in 39 by SHG and hysteroscopy. All 39 lesions were detectable during the ovulatory and early luteal phase (days 16–19) of the menstrual cycle. Accuracy of TVS during different phases was largely dependent on the size of the lesion. TVS falsely detected two lesions and missed fine adhesions in two patients.Conclusion: Accuracy of TVS in detection of IULs is highly dependent on the menstrual cycle phase, with the ovulatory and early luteal phase being the optimal time for this examination.Keywords: menstrual cycle phase, space occupying lesions, transvaginal sonography